Simulation Modeling of Train Traffic Based on GIS Technologies - Aripov, Nazirjon; Kamaletdinov, Shokrukh; Tokhirov, Nosir; Abduraxmanova, Zebo (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article we discuss the issue of simulation modeling of train traffic according to the normative schedule for train traffic using the special platform Any Logic. GIS technologies were used to visualize the movements of the rolling stock. Developed a special database inherent in the time elements of the train schedule. All types of actions of trains at the station and on the tracks are taken into account. Special agents have been created that make it possible to accurately reproduce the model after compilation. The result of this scientific work will be used to determine the impact of automated warning technologies on trains on main lines.